Public Health Program: Educating the Importance of Balanced Nutrition for Collective Well-being - Muh Barid Nizarudin Wajdi; Muhkamat Saini; Hisyam , Mohammad; S.A.P, Rangga Sa'adillah; Syah, Hafidza (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This study explores the impact of a community-based nutrition education program aimed at improving the knowledge and dietary practices of residents in Jatimulyo Village, Tanjunganom District, Nganjuk Regency, East Java. Using a Participatory Action Research (PAR) approach, the program engaged local residents, schoolchildren, and health workers in learning about balanced nutrition through workshops and interactive activities. The results demonstrated a significant increase in participants' knowledge about the importance of a balanced diet, with 70% of participants showing improved awareness of essential nutrients. Furthermore, the program led to positive changes in dietary practices, including increased consumption of fruits and vegetables and healthier cooking methods. Despite challenges such as cultural resistance and economic constraints, the program successfully empowered the community to adopt healthier eating habits. This study highlights the effectiveness of community-based nutrition education and its potential for improving public health in rural areas.